(untitled) (مجلة المنصور, 2023)
Image enhancement plays an important role in many machine vision applications such as noise smoothing and edge enhancing. Anisotropic diffusion filtering is a popular, and theoretically well understood, technique for denoising images such that it provides smoothing of intra-region areas preferentially over inter-region areas, thereby providing a good prospective tool for removing unwanted noise and preserving the edges of desired objects. In this paper a color image is enhanced using a new edge –stopping function for anisotropic diffusion algorithm to improve the performance of the anisotropic diffusion filter. The experimental results show that the new edge-stopping function of the anisotropic diffusion filter can gives better performance compared with the previously employed diffusivity functions for enhancing the colored image. The comparisons are based on Root Mean Square Error (RMSE), Peak Signal to Noise Ratio (PSNR), and Mean Structural Similarity Index value (MSSIM) measurements. Experiments show that the anisotropic diffusion filter with the new function can effectively remove noise from low PSNR images with minimum edge blurring.